Sustainability Analysis of Garlic Production in Sembalun District on Ecological, Economic and Social Dimensions - Febrilia, Baiq Rika Ayu; Usman, Abdullah; Hidayati, Asri; Hidayanti, Anna Apriana; Septiadi, Dudi; Danasari, Idiatul Fitri; Maulana, Salman Murod (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study aims to determine the sustainability category of garlic production in Sembalun District based on ecological, social and economic dimensions. The study was conducted in several villages in Sembalun District, East Lombok Regency, West Nusa Tenggara (NTB) Province, involving 50 garlic farmers. Data were collected using interviews based on questionnaires that had been developed and analysed using multidimensional scaling techniques. The study results showed that the ecological and social dimensions were in the good category, while the economic dimension was in the sufficient category. The results of the leverage analysis showed that the level of crop failure and the type of irrigation system attributes were the most sensitive attributes in the ecological dimension. Meanwhile, the attributes that influenced the social dimension were the attributes of participation in health insurance and the availability of farm labour. The two most sensitive attributes in the economic dimension were product marketing and seed prices.